(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In the present era, customer relationship marketing plays a vital role. The major goals of customer relationship marketing can be expressed simply as understanding and treating customers better for increased loyalty and profit. Main purpose of the study is examining the relationship between customer relationship marketing and customer satisfaction.There are contradicting views of researchers; in literature about the effectiveness of CRM practices and policies. Unfortunately, very little empirical data is there to prove the effectiveness of CRM practices in different industries. Therefore it becomes crucial for practitioners to clearly understand that how changes in the level of CRM practices and their effectiveness influence customer satisfaction and loyalty.The growing importance of relationship marketing has increased interest in the role of consumer trust and satisfaction in establishing, developing, and maintaining successful relational exchanges. There are many different relationship marketing tactics implemented for retaining customer. However, some of those tactics did not affect customer loyalty effectively, and switching behaviors frequently occur among most of targeted customers.